2021
DOI: 10.1007/s00261-021-03099-4
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of liver R2* quantification for liver iron quantification from cardiac R2* acquisitions

Abstract: Objectives To evaluate the reproducibility of liver R2* measurements between a 2D cardiac ECG-gated and a 3D breath-hold liver CSE-MRI acquisition for liver iron quantification. Methods A total of 54 1.5 T MRI exams from 51 subjects (18 women, 36 men, age 35.2 ± 21.8) were included. These included two sub-studies with 23 clinical MRI exams from 19 patients identified retrospectively, 24 participants with known or suspected iron overload, and 7 healthy volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…This study results show that, despite the differences in acquisition and fitting methods, R 2 * values obtained with 3D BH cGRE and 3D FB rGRE showed excellent agreement between each other and with biopsy‐calibrated 2D BH GRE across a wide range of HIC values, with slopes close to unity and very low mean biases. Further, the 95% LOA for both R 2 * and FF comparisons between the different acquisition methods in this study were similar as in the previously reported R 2 * and FF inter‐method and inter‐scanner reproducibility studies 19,32 . Notably, compared to 2D and 3D Cartesian fitting methods, the absence of magnitude noise correction for 3D rGRE did not lead to a strong bias in the R 2 * range, and for the acquisition parameters used in this study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study results show that, despite the differences in acquisition and fitting methods, R 2 * values obtained with 3D BH cGRE and 3D FB rGRE showed excellent agreement between each other and with biopsy‐calibrated 2D BH GRE across a wide range of HIC values, with slopes close to unity and very low mean biases. Further, the 95% LOA for both R 2 * and FF comparisons between the different acquisition methods in this study were similar as in the previously reported R 2 * and FF inter‐method and inter‐scanner reproducibility studies 19,32 . Notably, compared to 2D and 3D Cartesian fitting methods, the absence of magnitude noise correction for 3D rGRE did not lead to a strong bias in the R 2 * range, and for the acquisition parameters used in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Further, the 95% LOA for both R 2 * and FF comparisons between the different acquisition methods in this study were similar as in the previously reported R 2 * and FF inter-method and interscanner reproducibility studies. 19,32 Notably, compared to 2D and 3D Cartesian fitting methods, the absence of magnitude noise correction for 3D rGRE did not lead to a strong bias in the R 2 * range, and for the acquisition parameters used in this study. A recent study by Henninger et al performed in a large group of adult patients demonstrated a very good agreement (R 2 = 0.95) between R 2 * values obtained with 3D BH cGRE and those obtained with a different biopsy-calibrated 2D BH GRE method.…”
Section: Discussionmentioning
confidence: 75%
“…When T2* is transformed into reciprocal R2* (i.e., R2* [Hz] = 1000/T2* [ms]), it shows a strong correlation with hepatic iron deposition in the liver [ 20 ] as well as the breath-hold gradient echo (GRE)-based 2D and 3D T2*- and R2*-MRI. For these reasons, T2* is increasingly used to image the entire liver in a shorter acquisition time [ 21 ].…”
Section: Introductionmentioning
confidence: 99%